2013
DOI: 10.21608/jappmu.2013.71016
|View full text |Cite
|
Sign up to set email alerts
|

Sprouted Zea Mays on Date Palm Leaves and Potatoes Peel Waste Mixture and Its Effects on Performance of Desert Goats Under Dry Season in Sinai.

Abstract: The objectives of this study were to evaluate Sprouted techniques by planting white corn seeds (Zea Mays L.) on four roughage mixtures of date palm leaves (Phoenix dactylifera L.) and potatoes peels waste (Solanum tuberosum). Twenty five desert male goats averaged (eighteen months old) 22.76 ±1.29 kg live body weight were divided randomly into five equal groups (5 animals each) to receive one of the following experimental roughages R1: alfalfa (Medicago sativa) hay (control), R2: 75% potatoes peel waste (PPW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Highest digestibility coefficients of CP was recorded by animals fed T1 and T5 being 75.06 and 73.49%; respectively with no significantly differences between T3 and T4, while the lowest (P≤0.05) digestibility coefficients of CP was recorded by T2. These results agree with that obtained by Fayed (2011), Helal (2012, Helal and Mona (2013a), Helal and Mona (2013b) and Helal (2015) who found that the digestibility coefficients of all nutrients for sprouted barley on tested roughages were higher than that of untreated. This may be attributed to fresh grains sprouts have been reported to have highly soluble protein and amino acids in response to the enzymatic transformations during early plant growth (Chung et al, 1989 andDikshit andGhadle, 2003).…”
Section: Nutrient Digestion Coefficients and Nitrogen Balancesupporting
confidence: 92%
“…Highest digestibility coefficients of CP was recorded by animals fed T1 and T5 being 75.06 and 73.49%; respectively with no significantly differences between T3 and T4, while the lowest (P≤0.05) digestibility coefficients of CP was recorded by T2. These results agree with that obtained by Fayed (2011), Helal (2012, Helal and Mona (2013a), Helal and Mona (2013b) and Helal (2015) who found that the digestibility coefficients of all nutrients for sprouted barley on tested roughages were higher than that of untreated. This may be attributed to fresh grains sprouts have been reported to have highly soluble protein and amino acids in response to the enzymatic transformations during early plant growth (Chung et al, 1989 andDikshit andGhadle, 2003).…”
Section: Nutrient Digestion Coefficients and Nitrogen Balancesupporting
confidence: 92%